1990
DOI: 10.2214/ajr.154.1.2104705
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of femoropopliteal venous thrombosis with MR imaging: a comparison of four MR pulse sequences.

Abstract: Ave., Rochester, NV 14642. Address reprint requests to S. Totterman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Initial studies used contrast venography as gold standard and found sensitivity and/or specificity values for MRV as high as 100% in diagnosing femoro-popliteal DVT (55)(56)(57)(58). However, it has performed less well than contrast venography in assessing the calf veins.…”
Section: Mr Imaging Of Vtementioning
confidence: 99%
“…Initial studies used contrast venography as gold standard and found sensitivity and/or specificity values for MRV as high as 100% in diagnosing femoro-popliteal DVT (55)(56)(57)(58). However, it has performed less well than contrast venography in assessing the calf veins.…”
Section: Mr Imaging Of Vtementioning
confidence: 99%
“…Human venous thrombi have been de tected successfully by MRI [10,[17][18][19][20], and the outcome of thrombolytic treatment has been assessed by the same method [21], MRI is the only morphological method so far that can differentiate between retracted and nonretracted clots. Clot retraction hinders clot lysis in vitro, but the proof of the same effect in vivo is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…MR images of human venous thrombi showed regional variability in signal intensi ties [10]. This phenomenon was attributed to differences in thrombus age at different loca tions, but could also be explained by different degrees of retraction.…”
Section: Introductionmentioning
confidence: 94%
“…In the early 1990s magnetic resonance imaging (MRI) was tested in preliminary studies including those with a small number of patients. [58][59][60][61][62][63] Compared to contrast venography, they suggested that MRI was at least 90% sensitive and specific (review in 53…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%